Social Challenges Single Mother’s Confront in Raising their Children: Case study - Alatawi, Suhad Mohammed (Journal of Educational and Psychological Sciences, 2021)
This study aims to identify the social challenges a single mother faces during raising her children as well as the strategies she adopts to overcome these challenges. To achieve these aims, the researcher used a qualitative approach where interviews were conducted on four single mothers from Tabuk, Saudia Arabia. The data has been illustrated in light of the Social Role Theory which states that ’’ A role of a person is a model image of the social behavior that suites the situation and the expectation of the group’’ (Sergent 1965). The study has concluded that there are two common social challenges single mothers face during raising their children. i.e, gender role and social authority. Furthermore, the study has concluded that they adopt common strategies to confront these challenges. Based on such conclusions the researcher introduced some related recommendations.